2006
DOI: 10.1002/jcb.20780
|View full text |Cite
|
Sign up to set email alerts
|

Functional role of VDR in the activation of p27Kip1 by the VDR/Sp1 complex

Abstract: Our previous study demonstrate that vitamin D3 induces the binding of vitamin D3 receptor (VDR) to Sp1 transcription factor and stimulates p27Kip1 expression via the Sp1 consensus sequences in the promoter. Both VDR and Sp1 are transcriptional activators, it is unclear which protein functions as the transcription component of the VDR/Sp1 complex. To address this issue, we constructed the AF-2 deletion mutant of VDR and tested the effect of vitamin D3 on p27Kip1 expression. In consistent with our previous resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 31 publications
(26 reference statements)
1
26
0
2
Order By: Relevance
“…After silencing of MZF-1, as described in the legend to tion factors. Moreover, just as it has become clear that multiple transcription factors may interact with each other to modulate the expression of a wide variety of genes [52,53], this is also likely to be the case for CD11b and CD14 [54,55].…”
Section: Discussionmentioning
confidence: 96%
“…After silencing of MZF-1, as described in the legend to tion factors. Moreover, just as it has become clear that multiple transcription factors may interact with each other to modulate the expression of a wide variety of genes [52,53], this is also likely to be the case for CD11b and CD14 [54,55].…”
Section: Discussionmentioning
confidence: 96%
“…With respect to p27 Kip1 , the VDR functions as the transactivation component of the VDR-Sp1 complex to trigger the expression of its gene (Cheng et al 2006). Also, 1,25D-upregulation of CKI p27 Kip1 is blocked by a p38 inhibitor (Miura et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13] In addition to several oncogenes such as vascular endothelial growth factor, urokinase plasminogen activator, urokinase plasminogen activator receptor, and epithelial growth factor receptor, many tumor suppressor genes, such as p27 kip1 , p21 WAF1/CIP1 , p16 INK4 , and pp2a-c, are also induced by Sp1. [14][15][16][17][18][19][20] Further, many pro-apoptotic gene promoters, including fas, fas ligand, fax, and caspase 3, have been found to contain Sp1-binding elements. [21][22][23] Previous studies have revealed that upregulation of Sp1 transcriptional activity leads to Sp1 accumulation during tumorigenesis.…”
Section: Introductionmentioning
confidence: 99%